Electrodeposited Platinum Iridium Enables Microstimulation With Carbon Fiber Electrodes - della Valle, Elena; Koo, Beomseo; Patel, Paras R.; Whitsitt, Quentin; Purcell, Erin K.; Chestek, Cynthia A.; Weiland, James D. (Frontiers in Nanotechnology, 2021)
Ultrasmall microelectrode arrays have the potential to improve the spatial resolution of microstimulation. Carbon fiber (CF) microelectrodes with cross-section less than 8 $μ$m have been demonstrated to penetrate cortical tissue and evoke minimal scarring in chronic implant tests. In this study, we investigate the stability and performance of neural stimulation electrodes comprised of electrodeposited platinum-iridium (PtIr) on carbon fibers. We conducted pulse testing and characterized charge injection in vitro and recorded voltage transients in vitro and in vivo. Standard electrochemical measurements (impedance spectroscopy and cyclic voltammetry) and visual inspection (scanning electron microscopy) were used to assess changes due to pulsing. Similar to other studies, application of pulses caused a decrease in impedance and a reduction in voltage transients, but analysis of the impedance data suggests that these changes are due surface modification and not permanent changes to the electrode. Comparison of scanning electron microscope images before and after pulse testing confirmed electrode stability.